Challenge as Physician to Diagnose Pediatric Patient with Laryngopharyngeal Reflux: A case report and literature review - Rizki, Niken Ageng (Medicinus, 2020)
Background : Laryngopharyngeal reflux (LPR) is the reflux of backflow of gastric acid or refluxate that usually affects the throat and laryngopharynx. Many physicians are unable to differentiate between pediatric LPR with pneumonia. Laryngopharyngeal reflux needs to be widely known and understood by a physician because there are relationships between upper and lower airway disease. In pediatric, LPR may also contribute to many problems in the respiratory tract, the clinical manifestation of pediatric LPR, and remains a challenge for physicians.Objective : To emphasize the new diagnostic symptoms and signs instrument for pediatric LPR using a fiber-optic laryngoscope, also to remind the correlation between the upper and lower respiratory tract and factors which contribute to pediatric airway.Case : A case of a 21-month-old girl with sudden onset of hoarseness, stridor, and wheezing was diagnosed with pneumonia, further investigation showed reflux symptoms, vocal cord abnormalities, and subglottic edema that suggest LPR was the final diagnosis.Conclusion : Pediatric LPR may be difficult to diagnose, there are many differential diagnosis, symptoms, and signs that may occur. The new diagnostic instrument can be used for diagnosing pediatric LPR, it is feasible and applicable in daily practice. Laryngopharyngeal reflux needs to be understood and considered as a differential diagnosis for coughing, hoarseness, in children despite the diagnosis challenge.